Enhancement of photocurrent in an ultra-thin perovskite solar cell by Ag nanoparticles deposited at low temperature. Issue 3 (4th January 2017) - Liu, Yang; Lang, Felix; Dittrich, Thomas; Steigert, Alexander; Fischer, Christian-Herbert; Köhler, Tristan; Plate, Paul; Rappich, Jörg; Lux-Steiner, Martha Ch.; Schmid, Martina
Abstract : 22.2% relative enhancement of photocurrent in ultra-thin perovskite solar cells by one step incorporation of plasmonic silver nanoparticles. Abstract : Ultra-thin perovskite absorber layers have attracted increasing interest since they are suitable for application in semi-transparent perovskite and tandem solar cells. In this study, size and density controlled plasmonic silver nanoparticles are successfully incorporated into ultra-thin perovskite solar cells through a low temperature spray chemical vapor deposition method. Incorporation of Ag nanoparticles leads to a significant enhancement of 22.2% for the average short-circuit current density. This resulted in a relative improvement of 22.5% for the average power conversion efficiency. Characterization by surface photovoltage and photoluminescence provides evidence that the implemented silver nanoparticles can enhance the charge separation and the trapping of electrons into the TiO2 layer at the CH3 NH3 PbI3 /TiO2 interface. The application of these silver nanoparticles therefore has promise to enhance the ultra-thin perovskite solar cells.